2015
DOI: 10.1016/s1470-2045(14)71160-x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate versus deferred chemotherapy after radical cystectomy in patients with pT3–pT4 or N+ M0 urothelial carcinoma of the bladder (EORTC 30994): an intergroup, open-label, randomised phase 3 trial

Abstract: Lilly, Canadian Cancer Society Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
153
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(177 citation statements)
references
References 28 publications
2
153
1
11
Order By: Relevance
“…184 After a median followup of seven years, the absolute mortality rates were 47% for the adjuvant treatment group and 57% for the delayed treatment group. However, the difference was not statistically significant (adjusted HR 0.78, 95% CI 0.56-1.08; p=0.13).…”
mentioning
confidence: 94%
“…184 After a median followup of seven years, the absolute mortality rates were 47% for the adjuvant treatment group and 57% for the delayed treatment group. However, the difference was not statistically significant (adjusted HR 0.78, 95% CI 0.56-1.08; p=0.13).…”
mentioning
confidence: 94%
“…Patients were randomized to immediate treatment and deferred treatment groups. The study found no significant improvement in overall survival in the immediate treatment group compared to the treatment-deferred group [61]. This suggests that the timing of adjuvant or early salvage chemotherapy following cystectomy does not impact survival.…”
Section: Adjuvant Chemotherapymentioning
confidence: 80%
“…Accordingly, several large trials were planned to compare immediate adjuvant chemotherapy versus the same treatment administered at recurrence, or comparing adjuvant therapy versus sequential therapy. Like the preceding trials, all of these closed prematurely due to poor accrual, and thus they were unable to demonstrate a clear benefit of adjuvant chemotherapy [31,32].…”
Section: • Adjuvant Chemotherapymentioning
confidence: 99%